Complex advance care planning interventions for chronic serious illness: how do they work? a scoping review. Issue Volume 12:Issue e3(2022) (5th October 2021) - Stevens, Julie; Deliens, Luc; Pype, Peter; De Vleminck, Aline; Pardon, Koen
Abstract : Context: Advance care planning (ACP) interventions have the potential to improve outcomes for patients with chronic serious illness. Yet the rationale for outcome choices and the mechanisms by which outcomes are achieved are not always clear. Objectives: To identify and map proposed mechanisms on how complex ACP interventions can impact outcomes for patients with chronic serious illness and to explore factors that might explain intervention outcomes. Methods: This is a scoping review of randomised controlled trials of complex ACP interventions for patients with chronic serious illness which explicitly stated the mechanism(s) by which the intervention was thought to work. We searched six databases and hand-searched key journals and reference lists. Results: Inclusion yielded 16 articles. Inclusion procedures and mapping of mechanisms and outcomes indicated that causality between components and outcomes was not always clearly described. Tailoring intervention content to patients' needs was linked to the greatest number of different outcome categories, while promoting competence and confidence to engage in ACP was most often explicitly linked to a primary outcome. Three main factors which might have affected intended outcomes were identified: participant characteristics, such as illness experience or cultural differences; the setting of implementation; or methodological limitations of the study. Conclusion: Findings highlighted two main points of consideration for future ACP intervention studies: the need for clearly stated logic in how interventions are expected to impact primary outcomes and the importance of considering how an intervention may function for patients with chronic serious illnesses within a specific setting.